Integrating Traditional Ecological Knowledge and Frost Management Strategies for Sustainable Tree Planting in Legambo District, Ethiopia - Boja, Mesfin; Solomon , Bethelhem (Sustainability Science and Resources, 2025)
This study examines traditional ecological knowledge and tree planting practices in Legambo District, Ethiopia, focusing on local farmers' preferred tree species and their frost management techniques. With only two percent forest cover and significant frost affecting seedling survival, understanding these practices is vital for sustainable land management. Using a multistage sampling method, data were gathered from 42 households through interviews, questionnaires, and observations. The findings indicate that Eucalyptus globulus is the most favored tree species, accounting for 52% of planted trees, primarily in woodlots. The research underscores the serious impact of frost on young seedlings, especially on degraded hillsides, where farmers report high mortality rates. Additionally, various traditional frost management strategies were identified, such as mulching, building protective barriers, and careful watering. These practices reflect a deep understanding of local ecological conditions and highlight the need to combine traditional knowledge with modern forestry techniques. The study's implications extend beyond Legambo, contributing to broader discussions on sustainable land management in frost-affected areas of Ethiopia. It emphasizes the critical relationship between ecological factors and local agricultural methods, illustrating how farmers address environmental challenges. By investigating tree species selection and frost resilience, the research calls for adaptive management strategies suited to the region's needs. To improve tree survival and rehabilitate degraded areas, the study offers key recommendations, including regular monitoring of seedlings under one year, targeted training for farmers on frost management, and fostering community engagement to share successful practices. Ensuring access to quality planting materials is also essential. By encouraging collaboration among local communities, policymakers, and forestry practitioners, the study aims to bolster sustainable forestry efforts aligned with the region's ecological and socio-economic contexts.